Комбінована ресурсоефективна технологія заморожених плодово-ягідних напівфабрикатів - Сімахіна, Галина Олександрівна; Кочубей-Литвиненко, Оксана Валер'янівна (My University, 2023)
У нинішніх несприятливих умовах довкілля – роки пандемії Covid-19, воєнний стан – живі організми перебувають під постійним оксидантним стресом унаслідок дії вільних радикалів, реакційноздатних форм сполук кисню і прооксидантів, інших шкідливих чинників. І тому особливо важливою постає роль плодово-ягідної сировини як джерела сполук антиоксидантної дії – токоферолів, аскорбінової кислоти, фенольних сполук, каротиноїдів, ферментів, мікроелементів, ароматичних амінів тощо. Мета роботи – на основі теоретичних умовиводів та результатів експериментальних досліджень розробити універсальну технологічну схему отримання заморожених плодово-ягідних напівфабрикатів з різними модифікаціями та варіантами застосування штучного холоду і отриманням продукції, яка відповідає головним принципам харчування ХХІ століття – якість, безпека, ефективність. It is evident that all the live entities in current malignant environmental conditions (Covid-19 pandemic, military state) are exposed to constant oxidant stress due to the activity of free radicals, reactive forms of oxygen, prooxidants and other harmful factors. Therefore, the role of fruit and berry raw materials as the sources of antioxidant substances (tocopherols, ascorbic acid, phenol substances, carotenoids, enzymes, trace elements, aromatic amines, etc.) is gaining more importance. As a matter of fact, seasonality appears to be the conceptual disadvantage of fruit and berry raw materials .Hence the creation of reliable natural antioxidant protection for human body during the whole year is possible, providing that the raw is effectively preserved with maximal retention of all the valuable components of natural origin in the final products. Unfortunately, it is the antioxidant substances (primarily L-ascorbic acid) that undergo the utmost destruction, especially when it comes to berries with tender texture, like blueberries, raspberries or strawberries, which gets ruined in defrosting: in turn, it can result in the loss of cellular juice with antioxidants dissolved in it. Therefore, this work is aimed at improvement of the method to freeze fruit and berry cultures, which is the topical task oriented at the elaboration of multi-variant technology of high-quality frozen half products with proven expedience of selecting the certain freezing method, regarding the industrial conditions.
Keywords: кафедра технології оздоровчих продуктів; кафедра технології молока і молочних продуктів; консервування; штучний холод; кристалоутворення; кріопротектори; дефростація; антиоксиданти; preservation; artificial cold; crystal making; cryoprotectors; defrosting; antioxidants